Kreatif Membangun Daerah Melalui Pemanfaatan Teknologi Pada Masa Pandemi - fara fitriyani (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2022)
The Situation of the Implementation of Emergency Community Activity Restrictions (PPKM) due to the Covid-19 pandemic resulted in restrictions on community activities, including economic activities, educational activities, and other social activities. However, in this situation, the community is expected to remain productive and continue their activities while still complying with government regulations, namely the application of health protocols. The purpose of this activity is to empower the community through various aspects of development as an effort to achieve prosperity through the use of technology to develop the region creatively. This activity is carried out online. The results of the service carried out include activities related to the handling and prevention of covid 19, education, entrepreneurship, and the environment which are uploaded through youtube and social media so that the public can directly access the information submitted.